Fancy Nancy : Pajama day - O'Connor, Jane.; Preiss-Glasser, Robin; Enik, Ted; Bracken, Carolyn (New York : HarperCollins, 2009)
Nancy can't wait to wear her new nightgown for Pajama Day at school, until her best friends Bree and Clara show up wearing matching pink polka-dot pajamas.
Keywords: Pajamas -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Juvenile fiction; Vocabulary -- Juvenile fiction